Manajemen Pendidikan pada Keluarga Anak Tuli di Desa Bandung Sruni, Alian, Kebumen - Sarwiati Sarwiati; Fatatun Afifah; Silmi Muhimatul Chasanah; Tri Puji Lestari; Siti Fatimah; Agus Salim Chamidi (Lembaga Bale Literasi, 2022)
Deaf is a person who has lost his ability to hear due to the malfunction of part or all of his hearing apparatus. Educating deaf children is different from educating normal children. The purpose of the study was to analyze the education management of families of deaf children in Bandungsruni Village, Alian, Kebumen. The type of research used is qualitative research using the ethnographic method of communication. The implementation of research activities lasted for 1 month, namely in March 2022. The data collection techniques used observation, interviews, and documentation techniques. The data analysis technique uses the Miles and Huberman model. The results of the analysis show that deaf families in Bandungsruni Village, Alian in terms of education given by parents to their children are very large. The education management function in the family has also been running well starting from planning, implementation, and evaluation. The parenting pattern in the family adheres to a democratic parenting pattern that has a good impact on the development of deaf children.